2020
DOI: 10.1016/j.stem.2020.06.015
|View full text |Cite
|
Sign up to set email alerts
|

A Human Pluripotent Stem Cell-based Platform to Study SARS-CoV-2 Tropism and Model Virus Infection in Human Cells and Organoids

Abstract: Highlights d A hPSC-derived cell and organoid platform is used to study SARS-CoV-2 tissue tropism d Human pancreatic alpha and beta cells are permissive to SARS-CoV-2 infection d Human hepatocyte and cholangiocyte organoids are permissive to SARS-CoV-2 infection d hPSC-derived cells/organoids show similar chemokine responses as COVID-19 tissues

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
722
3
30

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 591 publications
(785 citation statements)
references
References 53 publications
30
722
3
30
Order By: Relevance
“…In addition, the range of different cell types detected as infected by SARS-CoV-2 keep expanding (e.g. 173,174,175,176 ) . We thus do think that this apparent limitation could be also seen as an asset of our study; (ii) In our opinion, the main limitation This first proximal interaction mapping of SARS-CoV-2 proteins provides a plethora of novel research tracks to better understand this virus pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the range of different cell types detected as infected by SARS-CoV-2 keep expanding (e.g. 173,174,175,176 ) . We thus do think that this apparent limitation could be also seen as an asset of our study; (ii) In our opinion, the main limitation This first proximal interaction mapping of SARS-CoV-2 proteins provides a plethora of novel research tracks to better understand this virus pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate whether organoids from different tissues exhibit similar transcriptional responses upon SARS-CoV-2 infection, we compared SARS-CoV-2 induced transcriptional changes among CPOs and published datasets from hepatocyte organoids (Yang et al, 2020a) and intestinal organoids (Lamers et al, 2020). Surprisingly, we found little overlap among upregulated or downregulated genes in the three different organoid types, suggesting a predominantly cell typespecific response to SARS-CoV-2 infection ( Figure 4E).…”
Section: Transcriptional Dysregulation Of Choroid Plexus Organoids Upmentioning
confidence: 98%
“…Additionally, these cultures were useful in screening for drugs to treat ZIKV infection (Xu et al, 2016). Recently, hiPSC-derived organoids have been used to model SARS-CoV-2 infection in many organs, including the intestine, lung, kidney, liver, pancreas, and vasculature (Lamers et al, 2020;Monteil et al, 2020;Yang et al, 2020a;Zhou et al, 2020). These studies have shown that SARS-CoV-2 can infect and replicate within cells of multiple organs, leading to transcriptional changes indicative of inflammatory responses and altered cellular functions.…”
Section: Introductionmentioning
confidence: 99%
“…Given the fact that ACE2 is expressed on pancreatic β-cells and ACE2 is the main receptor for COVID-19 (Sars-CoV-2) internalization we would like to propose a direct cytolytic β-cell damage due to COVID-19 (Sars-CoV-2) resulting in an insulin-depended diabetes without a classical autoimmune pathology in our patient. This assumption is supported by a recent mechanistic study demonstrating that adult human pancreatic alpha and beta cells are permissive to Sars-CoV-2 pseudo-entry virus and Sars-CoV-2 virus infection [14] . Furthermore, Sars-CoV-2 infection of pancreatic endocrine cells resulted in robust chemokine induction as seen in Covid-19 patients and upregulation of markers of cell death [14] .…”
Section: Discussionmentioning
confidence: 73%
“…This assumption is supported by a recent mechanistic study demonstrating that adult human pancreatic alpha and beta cells are permissive to Sars-CoV-2 pseudo-entry virus and Sars-CoV-2 virus infection [14] . Furthermore, Sars-CoV-2 infection of pancreatic endocrine cells resulted in robust chemokine induction as seen in Covid-19 patients and upregulation of markers of cell death [14] .…”
Section: Discussionmentioning
confidence: 73%